Rigorism of Truth : "Moses the Egyptian" and Other Writings on Freud and Arendt - Blumenberg, Hans (Book collections on Project MUSE., 2018)
"In 'Moses the Egyptian'--the centerpiece of this book--the German philosopher Hans Blumenberg addresses two defining figures in the intellectual history of the twentieth century: Sigmund Freud and Hannah Arendt"--Provided by publisher.